Repeated stimulus exposure alters the way sound is encoded in the human brain. - Kelly L Tremblay; Kayo Inoue; Katrina McClannahan; Bernhard Ross (PLoS ONE)
Auditory training programs are being developed to remediate various types of communication disorders. Biological changes have been shown to coincide with improved perception following auditory training so there is interest in determining if these changes represent biologic markers of auditory learning. Here we examine the role of stimulus exposure and listening tasks, in the absence of training, on the modulation of evoked brain activity. Twenty adults were divided into two groups and exposed to two similar sounding speech syllables during four electrophysiological recording sessions (24 hours, one week, and up to one year later). In between each session, members of one group were asked to identify each stimulus. Both groups showed enhanced neural activity from session-to-session, in the same P2 latency range previously identified as being responsive to auditory training. The enhancement effect was most pronounced over temporal-occipital scalp regions and largest for the group who participated in the identification task. The effects were rapid and long-lasting with enhanced synchronous activity persisting months after the last auditory experience. Physiological changes did not coincide with perceptual changes so results are interpreted to mean stimulus exposure, with and without being paired with an identification task, alters the way sound is processed in the brain. The cumulative effect likely involves auditory memory; however, in the absence of training, the observed physiological changes are insufficient to result in changes in learned behavior.